Сомовые рыбы северо-западной части Индийского океана (определитель). Сообщение II - Дмитренко, Е.М. (Вестник зоологии, 1969)
The article deals with an attempt to give as a determinant the description of a specific composition of fish from the Ariidae and Plotosidae families in the north-western part of the Indian ocean. The materials, on which the determinant is based, were gathered in cruises on the Soviet fishery, research and searching ships beyond the limits of territorial waters of various states at depths of 20—100 m. The data from the foreign literature on this group of fish are also used in the paper. In two communications (Communication I see in <Zoological Record» No. 6, 1968) the description of the two above-mentioned families, five genera and 18 species of Siluroidei is presented.